The Effectiveness Saffron Tea on Reducing Stress Level Among Nursing Student - Sumiyarini, Retno; Diaz, Khristina (Jurnal EduHealth, 2022)
Globally, around 60% of college students perceived stress. Untreated stress will have a negative impact on students’ quality of life, moreover, it can trigger students to consume drugs and alcohol, or commit suicide. Students’ reluctance to seek help, expensive treatment cost, and long treatment times to reduce stress encouraged us to assess the effects of saffron as an alternative treatment on reducing stress among students. The aim of this study was to evaluate the effect of saffron on students who perceive stress. We conducted an un-blinded experimental study. We recruited 78 nursing students who perceive stress, divided into two groups, the saffron group (n=42) and control groups (n=36). Treatment protocol was: saffron group received saffron as brewed drinks, while control group drinks regular tea. The treatment duration is two weeks. Using the DASS 21 Checklist, we assessed the students at baseline, and after 2 weeks completed therapy to measure the outcome. Finally, the data were analyzed using t test statistical analysis. Saffron had a more significant impact on the stress level among the intervention group. The mean stress scores decreased from 15.4 ± 6.1 to 10.8 ± 5.8 for the saffron group (p < .0001) and from 15.6 ± 5.7 to 14.7 ± 6.4 for the control group (p < .01). Our findings suggest that saffron is as effective to reduce stress level among nursing students